(untitled) (Scientific journal of the Fergana State University, 2025)
The article theoretically presents the views on the great scientist Abu Ali ibn Sino, who made an incomparable contribution to world culture, a naturalist, philosopher, sage of medical science, astronomer, mathematician, musician, writer and poet, and his importance in moral and educational issues today. It is analyzed that this article will have great ideological, political and practical significance in subsequent scientific activities in glorifying and elevating the genius of Abu Ali ibn Sino.